Pendidikan Madrasah di Indonesia dalam Potret Waktu: Studi atas Sejarah Perkembangan Madrasah di Indonesia - Abdul Kirom; Imroatul Imamiyah (Maharot : Journal of Islamic Education, 2021)
Previously, madrasas were only in the form of assemblies of the Prophet centered in the city of Mecca, either in mosques or at the homes of several friends. Called madrasas because madrasas are schools or colleges based on Islam. Madrasas that entered Indonesia during the Dutch East Indies colonial period were madrasas in the form of pesantren, because Islamic boarding schools in Indonesia were educational institutions that taught Islam, which was the incarnation of the Prophet's assembly in Mecca. Over time, madrasas (in Indonesia, which were pesantren at that time) were required to be formalized in the unit curriculum system by the state government. Therefore, now gradually, after being repeatedly demanded to move in a formal direction, madrasas are known from the RA, MI, MTs., MA and MAK levels. Most of them are still under the auspices of pesantren because the original meaning of pesantren is a reflection of the forerunner of madrasas, the two of which are still difficult to separate from one another to this day.